流体抵抗と慣性を同時に満たす集中定数系モデルの導出と基本的流路形状における検証 - 清水, 文雄; 田中, 和博; 肥後, 寛 (日本フルードパワーシステム学会論文集, 2021)
A laminar flow resistance in a pipe is usually used as a representative model of flow resistance because it is convenient to use and often gives reasonable resistance value in a small size pipe under steady state condition. However, the laminar flow resistance model in a pipe is not applicable in an oil flow passage of a real circuit because a flow passage has complex shape in a real circuit. Furthermore, the mathematical model of fluid column in a pipe made in inviscid flow condition is often used as an inertial model in considering dynamic condition. In the real condition of operating oil-hydraulic circuit, the above mentioned two effects, a complex shape of flow passage and flow dynamic characteristics, appears in viscous flow condition. A new model or modeling method to include and solve these effects reasonably becomes necessary. A new modeling method using CFD is introduced in this paper.